283 AN EXPLORATION OF THE IRISH NATIONAL FRAILTY EDUCATION PROGRAMME ON PRACTICE: A FRAILTY FACILITATOR'S PERSPECTIVE. (25th October 2022) - Munro, F; Murphy, C
Abstract: Background: Frailty is associated with a range of adverse outcomes in older adults requiring prevention, early detection and management. Interprofessional collaboration in education and practice can facilitate integrated care for older people in the management of frailty. In Ireland, an interprofessional National Frailty Education Programme (NFEP) is delivered in partnership between the National Clinical Programme for Older People (NCPOP) and The Irish Longitudinal Study on Ageing (TILDA). On completion of the NFEP, Frailty Facilitators return to their regional/local frailty networks to deliver the programme to healthcare professionals across disciplines and settings. The aim of this study is to explore the impact of the National Frailty Education Programme on practice. Methods: A qualitative exploratory approach was adopted to elicit the perspectives of Frailty Facilitators on the impact of the NFEP on practice. Purposive sampling was employed across frailty networks nationwide. Focus groups were conducted, and data were analysed using thematic analysis. Results: Twenty-four participants from five frailty networks took part in five focus groups across Ulster, Leinster and Connaught. Frailty Facilitators collaborated to deliver education on frailty in their local networks following the NFEP. Management support particularly that provided by the Centres for Midwifery and Nurse Education was deemed a significant enabler of frailty education. Strong interprofessional alliances were developed that enhanced communication between primary and secondary care settings in the care of older people. The medical profession were noted to have low participation in the frailty networks. The results revealed widespread use of frailty instruments for assessment and a shared understanding and language on frailty. Conclusion: The NFEP had a clear impact on Frailty Facilitator's practice. Conceptualisation and reflection on frailty related practice was in evidence across the frailty networks thus enabling multidisciplinary teams to manage the care of an older person with frailty in an integrated way.